2015
DOI: 10.15184/aqy.2015.127
|View full text |Cite
|
Sign up to set email alerts
|

Digital imaging and prehistoric imagery: a new analysis of the Folkton Drums

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 22 publications
1
18
0
2
Order By: Relevance
“…The evidence of erasure of 'eyebrow' motifs recently recorded on drum II ( Fig. 2; Jones et al 2015) suggests that differentiation of designs amongst the group of artefacts took place 'on the fly' during the act of making and carving.…”
Section: The Folkton Drumsmentioning
confidence: 91%
See 2 more Smart Citations
“…The evidence of erasure of 'eyebrow' motifs recently recorded on drum II ( Fig. 2; Jones et al 2015) suggests that differentiation of designs amongst the group of artefacts took place 'on the fly' during the act of making and carving.…”
Section: The Folkton Drumsmentioning
confidence: 91%
“…This visual tradition is shared with northern Portugal and Galicia, northern Spain (Alves 2012), where these abstract images are combined with representational images of zoomorphs (mainly deer), weaponry and the occasional anthropomorph (Fabregas Valcarce & Rodriguez-Rellán 2015). More complex motifs, such as rosettes, double spirals, stars and nested arcs are shared between passage tombs, certain open-air rock-art panels, pottery and decorated artefacts in Britain and Ireland (Bradley 1997;Cochrane et al 2015;Jones et al 2011), while some of these motifs-such as nested arcsare also found in French passage tombs (Shee Twohig 1981). Recent excavations around rock-art sites in Britain have produced Neolithic dates (Bradley et al 2012;Jones et al 2011)…”
Section: After the Eye Goddessmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure of recording described here is undoubtedly a resource for assessing the sequences of use of menhirs and "stelae-menhirs". As other megalithic slabs (Bueno-Ramírez et al, 2016) or objects (Jones et al, 2015), menhirs and "stelae-menhirs" are the final result of a series of tasks that might include the re-making, transformation and maintenance of monuments, whose display and exhibition must have played a relevant role.…”
Section: Discussionmentioning
confidence: 99%
“…H-RTI metodunun kültürel miras araştırmalarına adapte edilmesiyle birlikte RTI kullanımı ivme kazanmaya başlamış ve son on yılda metodun yer aldığı proje ve araştırmalar büyük oranda artış göstermiştir. Metodun özellikle; prehistorya(Pitts et al 2014;Jones et al 2015), kaya sanatı(Mudge et al 2006;Duffy 2010;Mudge et al 2012), epigrafi (Kleinitz 2012; Kleinitz 2013; Piquette 2014; Tüner-Önen & Akçay 2014), konservasyon(Earl et al 2010;Artal-Isbrand et al 2011;Tamayo et al 2013), numismatik(Mudge et al 2005;Diaz-Guardamino & Wheatley 2013), paleontoloji(Newman 2014) etc. birçok disipline adapte edildiği ve materyallerin belgeleme ve analizine pozitif katkılar sunduğu bilimsel çalışmalarla deneyimlenmiştir.…”
unclassified